(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article shows a generalized method of calculating the forces and means necessary for the organization of the evacuation of the population from the area where emergency situations have occurred, as well as for the elimination of the emergency situation.